2018
DOI: 10.1194/jlr.m082388
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible lipid droplet-associated protein inhibits adipose triglyceride lipase

Abstract: Elaborate control mechanisms of intracellular triacylglycerol (TAG) breakdown are critically involved in the maintenance of energy homeostasis. Hypoxia-inducible lipid droplet-associated protein (HILPDA)/hypoxia-inducible gene-2 (Hig-2) has been shown to affect intracellular TAG levels, yet, the underlying molecular mechanisms are unclear. Here, we show that HILPDA inhibits adipose triglyceride lipase (ATGL), the enzyme catalyzing the first step of intracellular TAG hydrolysis. HILPDA shares structural similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 39 publications
2
40
0
Order By: Relevance
“…As an antipode for CGI-58, G0/G1 switch gene 2 ( G0S2 ) potently inhibits ATGL activity by direct protein-protein interaction and through impeding substrate accessibility [ 46 ]. Recently, it has been shown that ATGL is profoundly inhibited by a small protein called hypoxia-inducible LD-associated protein ( HILPDA , also known as hypoxia inducible gene 2, HIG2) which directly binds to the patatin domain of ATGL [ 47 , 48 ]. Another player in the team of ATGL regulators is pigment epithelium-derived factor ( PEDF ).…”
Section: Update On Atgl Biochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…As an antipode for CGI-58, G0/G1 switch gene 2 ( G0S2 ) potently inhibits ATGL activity by direct protein-protein interaction and through impeding substrate accessibility [ 46 ]. Recently, it has been shown that ATGL is profoundly inhibited by a small protein called hypoxia-inducible LD-associated protein ( HILPDA , also known as hypoxia inducible gene 2, HIG2) which directly binds to the patatin domain of ATGL [ 47 , 48 ]. Another player in the team of ATGL regulators is pigment epithelium-derived factor ( PEDF ).…”
Section: Update On Atgl Biochemistrymentioning
confidence: 99%
“…In humans, ATGL is also activated by CGI-58 [ 39 , 51 ] and inhibited by G0S2 [ 52 ] and HILPDA [ 48 ] ( Fig. 1 ).…”
Section: Update On Atgl Biochemistrymentioning
confidence: 99%
“…HILPDA directly binds and inhibits ATGL in vitro [75,77]. The contact region between HILPDA and ATGL was mapped to the hydrophobic N-terminus of HILPDA and the patatin domain of ATGL [77]. Consistently, deleting the amino acid region Leu7 to Gly11 in HILPDA completely abolishes its binding to ATGL [75].…”
Section: Hypoxia-inducible Ld-associated Protein (Hilpda)mentioning
confidence: 89%
“…HILPDA is structurally similar to G0S2, is ubiquitously expressed upon hypoxia, and localizes to the LD [74][75][76]. HILPDA directly binds and inhibits ATGL in vitro [75,77]. The contact region between HILPDA and ATGL was mapped to the hydrophobic N-terminus of HILPDA and the patatin domain of ATGL [77].…”
Section: Hypoxia-inducible Ld-associated Protein (Hilpda)mentioning
confidence: 99%
See 1 more Smart Citation